PENGARUH PSYCHOLOGICAL WELL BEING (PWB) TERHADAP MOTIVASI BERPRESTASI MAHASISWA DI ERA PANDEMI - Grahani, Firsty Oktaria; Mardiyanti, Ressy; Sela, Nina Permei; Nuriyah, Sinta (Esa Unggul University, 2021)
AbstractIn this era of the Covid-19 pandemic, learning is carried out online (on a network) to stop the spread of Covid-19, so students are required to be able to manage their achievement motivation in learning, because learning is not done face-to-face. At this time, achievement motivation is one of the important aspects that must be possessed by students in order to achieve optimal learning competencies. According to Nakayama et al (2014) that all literature indicates that not all students will be successful in online learning, this is due to differences in learning environment factors and student characteristics. The online learning policy demands adaptation to the teaching and learning process accompanied by high motivation, independence and responsibility for learning as reflected in the psychological well being of students. Based on this opinion, it can be interpreted that psychological well being is related to efforts to fulfill and realize basic human nature through the process of self-actualization of their potentials, so it is hoped that students who have high psychological well being will have high achievement motivation so that they are not hampered by the existence of pandemic conditions. Therefore, researchers want to further examine the influence of Psychological Well Being on Student Achievement Motivation in the Pandemic Era. The purpose of this study was to determine the effect of Psychological Well Being on student achievement motivation in the Pandemic Era and to obtain an overview of the dynamics of Psychological Well Being on student achievement motivation in the pandemic era. This research is a descriptive study with a sample of students who have at least one year of study at Wijaya Putra University. The sampling technique used was accidental sampling (non-probability test) with data analysis techniques using regression analysis techniques. The results of the hypothesis test show that sig = 0.000 <0.05, which means that there is an influence between psychological well being on achievement motivation. R square = 0.607 indicates that psychological well being has an influence of 60.7%, while 39.3% is influenced by other variables.